An Experimental Optimization Research of Methyl and Ethyl Esters Production from Safflower Oil - Gulum Mert; Bilgin Atilla (Environmental and Climate Technologies, 2018)
Nowadays, biodiesel is drawing attention as a renewable and clean alternative to fossil diesel fuel because of numerous advantages such as higher flash point, cetane number and density. However, the high viscosity of biodiesel is one of the critical shortcomings and it causes poor atomization, decrease in engine performance and increase in exhaust emissions. To overcome this shortcoming, in this study, the effects of main transesterification reaction variables on the viscosities of produced safflower oil methyl and ethyl esters (biodiesel) were investigated as a full factorial experimental design, and optimum parametric values giving the lowest viscosity were determined. Density and viscosity were measured according to ISO 4787 and DIN 53015 standards. Sodium ethoxide (C2H5ONa) was utilized as a catalyst, and 90 and 120 minutes of reaction duration were kept constant for methanolysis and ethanolysis reactions. According to the results, the optimal reaction parameters were determined as: 0.75 % catalyst concentration, 8:1 alcohol to oil molar ratio and 56 °C reaction temperature for methanolysis; 1.00 % catalyst concentration, 12:1 alcohol to oil molar ratio and 70 °C reaction temperature for ethanolysis. Based on the reaction parameters, the methyl and ethyl esters were produced with the lowest viscosities of 3.989 mm2/s and 4.393 mm2/s, respectively. In the light of results obtained in this study, similar studies on production of biodiesels from different oils and alcohols can be performed.